1999
DOI: 10.1046/j.1469-8137.1999.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of elevated [CO2] and drought on cherry (Prunus avium) seedlings II. Photosynthetic capacity and water relations

Abstract: Cherry seedlings (Prunus avium) were grown from seed for two growing seasons in three ambient [CO # ] ("350 µmol mol −" ) and three elevated [CO # ] (ambient j"350 µmol mol −" ) open-top chambers, and in three outside blocks. A drying cycle was imposed in both the growing seasons to half the seedlings : days 69-115 in the first growing season, and in the second growing season days 212-251 on the same seedlings which had already experienced drought. Stomatal conductance was significantly reduced in eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
2
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 42 publications
6
38
2
1
Order By: Relevance
“…A similar lack of response in leaf water potential to elevated [CO 2 ] was observed by Ferris & Taylor (1994) and Ellsworth (1999), albeit in the latter study with loblolly pine, a significant response might not have been expected given that no effect of atmospheric [CO 2 ] on stomatal conductance was observed. Although it is not surprising that some studies report no effect of elevated [CO 2 ] on leaf water potential, it is interesting that a few recent studies have shown that leaf water potentials may actually be lower (more negative) in plants grown at elevated [CO 2 ] (Centritto et al 1999b;De Luis et al 1999). The mechanisms that contribute to these effects are not known.…”
Section: Reductions In Stomatal Conductance and Impacts On Leaf Watermentioning
confidence: 88%
See 2 more Smart Citations
“…A similar lack of response in leaf water potential to elevated [CO 2 ] was observed by Ferris & Taylor (1994) and Ellsworth (1999), albeit in the latter study with loblolly pine, a significant response might not have been expected given that no effect of atmospheric [CO 2 ] on stomatal conductance was observed. Although it is not surprising that some studies report no effect of elevated [CO 2 ] on leaf water potential, it is interesting that a few recent studies have shown that leaf water potentials may actually be lower (more negative) in plants grown at elevated [CO 2 ] (Centritto et al 1999b;De Luis et al 1999). The mechanisms that contribute to these effects are not known.…”
Section: Reductions In Stomatal Conductance and Impacts On Leaf Watermentioning
confidence: 88%
“…Thus, CO 2 enrichment studies that link plant and soil-based processes should be encouraged. (Centritto et al 1999b) A common expectation from many, albeit not all, studies that address the physiological response of plants to elevated [CO 2 ] is that stomatal conductance will be reduced. In herbaceous species, these reductions can approach 27-40% (Morison 1985;Field et al 1995), whereas in some coniferous species the response may be considerably less (Teskey 1995;Tissue et al 1997;Ellsworth 1999).…”
Section: Enhanced Water-use Efficiency and Consequences For Drought Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Clifford et al, 1995;Heckenberger et al, 1998;Pa Èa Èkko Ènen et al, 1998). Some studies, however, report no response (Estiarte et al, 1994;Dixon et al, 1995;Pritchard et al, 1998;Centritto et al, 1999). No studies report a decrease.…”
Section: Water Stressmentioning
confidence: 99%
“…A second limitation is the possible effect of elevated CO 2 on stomatal conductance, resulting in reduced transpiration and demand for water (Drake et al 1997). Although there is little direct, experimental evidence that fruit trees display reduced transpiration in response to elevated CO 2 (Centritto et al 1999(Centritto et al , 2002, there is considerable evidence that grasses and other annual C3 crops transpire less in elevated CO 2 atmospheres (Morison 2001). Such reductions in water demand may be as high as 20-30%, although a study of potential effects of climate change on US agriculture determined that un-irrigated field crops (corn, wheat, alfalfa) grown in the Pacific Northwest and western mountainous regions had relatively low decreases in transpiration by the end of the current century (approximately 8%) compared with other regions (Izaurralde et al 2003).…”
Section: Risk Assessmentmentioning
confidence: 99%